ChemInform Abstract: Conformationally Restricted Functionalized Heteroaromatics: A Direct Access to Novel Indoloindoles via Pd‐Mediated Reaction. Issue 36 (15th August 2013) - Prasad, Bagineni; Sreenivas, B. Yogi; Rambabu, D.; Krishna, G. Rama; Reddy, C. Malla; Kumar, K. Lalith; Pal, Manojit
Abstract With a view to find novel inhibitors of sirtuins, a series of indolo[2, 3‐b]indoles (IV) is prepared by a palladium‐catalyzed intramolecular cyclization of iodides (III).